Change in biodiversity and abundance of benthic foraminifera with distance from the Rainbow hydrothermal vent field, Mid-Atlantic Ridge - H. Krüger; H. Krüger; G. Schmiedl; G. Schmiedl; Z. Steiner; Z. Zhang; E. P. Achterberg; N. Glock (Journal of Micropalaeontology)
In the vicinity of hydrothermal vent fields, unique habitats are observed that are influenced by hydrothermal fluids. Benthic foraminifera can be part of the communities found around these hydrothermal vent fields. They can form suitable indicators for different marine environmental conditions because their tests are often well preserved in the sediments. In this work, living (rose-bengal-stained) and dead benthic foraminifera from six sediment core tops were investigated with increasing distance from the Rainbow hydrothermal vent field at the Mid-Atlantic Ridge. The proximal-to-distal transect was sampled starting at ∼ 200 m distance from the active vents and followed the vent plume for ∼ 41 km. The biodiversity and abundance of benthic foraminifera tended to increase with distance from the Rainbow hydrothermal vent field, and there was a significant difference between the living and dead assemblage. The Shannon–Wiener diversity was lower at 0.2–1 km distance from the vent field with 2.3 (living) and 2.8 (dead) and showed higher constant values of 3.0 to 3.3 (living) and ∼ 3.6 (dead) from a distance of ∼ 2 km onwards. The population density of living benthic foraminifera showed a similar pattern to the biodiversity, while the density of empty foraminiferal tests was subject to strong fluctuations. Differences in the species composition between live and dead assemblages indicate environmental fluctuations, which could be triggered by seasonal nutrient pulses or brief contacts of the vent plume with the sediment. Species composition changed with distance from the black smokers. While miliolids dominated sediments closer to the vent field, hyaline perforate and agglutinated species constituted the major parts of the assemblages at greater distances. Thus, miliolids may be better adapted to the environment potentially influenced by hydrothermal vent fluids than the hyaline and agglutinated species. Specifically, miliolids seem to tolerate elevated porewater concentrations of copper, cobalt, and zinc and are possibly influenced by intrusions of acidic hydrothermal fluids. This result is in contrast to studies from other venting sites with acidic fluids, where agglutinated species dominate. High biodiversity and abundances of benthic foraminifera suggest that a diverse benthic ecosystem occurs below the distal Rainbow vent plume.